PERBANDINGAN HUKUM MENGENAI TINDAK PIDANA PENCURIAN MENURUT HUKUM INDONESIA DENGAN HUKUM IRLANDIA - Irsyad Aditya Purnomo Putra; Fachri Bey (Reformasi Hukum Trisakti, 2022)
The crime of stealing or the crime of theft is the type of crime that frequently occurs in society. Because there are so many distinct tribes and races in the Indonesian state, each with its own personalities and traits, crime must be closely watched. Like Indonesia, Ireland is not immune to theft-related crimes. How are the similarities and differences in the crime of stealing according to the Criminal Code and Criminal Justice Ireland is the formulation of the issue discussed in this study. While utilizing secondary data found through library research, the research approach adopts a normative juridical research type. Deductive reasoning was used to qualitatively examine secondary data. The study's findings, analysis, and recommendation, specifically the parallels, are in the  findings of the study, along with the discussion and conclusion, show that while there are differences in the country's legal system, criminal penalties, the number of articles, how those articles are applied, and penalties for losing rights, there are similarities in the manner in which theft is committed, the losses incurred as a result of the crime, and the purpose of theft. Ireland and Indonesia have significantly distinct legal systems, with Ireland adhering to the common law system and Indonesia following the civil law system. Ireland, meanwhile, adheres to the common law system of law.